Making it work: Institutionalizing digitalization in Danish local administrations - Blinkenberg Federspiel, Sofie (Scandinavian Journal of Public Administration, 2015)
Digitalization is held to be a key component in transforming the public administration into a reflexive, flexible and dynamic organization. For this to be realized, digitalization, i.e. the strategic use of Information Technology (IT) in innovating workflows, needs to become a part of the organizational identity. Drawing on the concepts of institutional logics and institutional work this paper uses a qualitative case study of two Danish local administrations to explore the institutionalization of digitalization. The paper describes the intra-organizational presence of diverging perceptions of the role of IT in digitaliza- tion and illustrates how institutional work within the organizations was loosely organized around specific characters – the Mediators, the Preachers and the Gatekeepers – with the purpose of bridging these differences into a nuanced institution of digitalization. By showing that the organization of institutional work within an organization is not only shaped by but also a strategic response to diverging institutional logics, the paper makes an important contribution to the debate on the relation between institutional work and institutional logics. The findings make the paper urge the local administrations to accept a more nuanced institutionalization of digitalization, and to highlight the key role, the mid- level manager as a Mediator plays in this regard.